Kegiatan Rutinitas Sholawat sebagai Media Pendidikan Karakter Religius Remaja di Desa Jatikalang Krian Sidoarjo (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
The routine prayer recitation activity with teenagers in Jatikalang Village, Krian, Sidoarjo, essentially arose from the need for moral development among teenagers amidst today's increasingly complex and externally influenced lives. Through this activity, it is hoped that teenagers can become closer to religious values ​​without feeling patronized, as the activities are simple and relevant to their daily lives. Furthermore, a sense of community among teenagers is fostered, becoming more than just a form of worship but also a positive gathering space. The implementation itself uses an Asset-Based Community Development (ABCD) approach, emphasizing existing community potential, such as the role of administrators, youth involvement, and available village facilities. The activity is relatively simple, starting with an opening and reciting prayers, rowi Diba' (the prayer of the Prophet), mahalul qiyam (the prayer of the Prophet), and closing with a short sermon (kultum) usually containing light but impactful messages. These activities are beginning to show changes: teenagers are becoming more active, a sense of togetherness is growing, and good habits such as discipline, mutual respect, and responsibility are gradually emerging. Furthermore, this activity serves as an alternative to prevent teenagers from getting caught up in less beneficial activities. There are still challenges, particularly with fluctuating attendance and the strong influence of the external environment. However, if maintained and developed consistently, this activity has great potential to become a platform for social and spiritual development for youth. Overall, this sholawat routine is quite effective in developing religious character and strengthening social ties within the community.